THE APPEARANCES OF CODE SWITCHING AND CODE MIXING IN ONLINE CONVERSATION - I Dewa Ayu Agung Radhaswati; Putu Kerti Nitiasih (Undiksha Press, 2022)
Code switching and code mixing are occurred due to phenomena of bilingualism and multilingualism in communication activity. The use of code switching and code mixing are generally used when people talk to each other with friends, family, or other people. This study aimed to analyze the types of code switching by Poplack (1980) such as Intra sentential, Inter sentential and Extra sentential and code mixing by Muysken (2000) which consists of Insertion, Alternation and Congruent lexicalization which is occurred in the conversation in the conversation between Najwa Shihab and Maudy Ayunda in the “Catatan Najwa” Youtube channel. This study also analyzed type of reasons of code switching and code mixing occurred in the conversation. The mixes of qualitative and quantitative method were used by the researcher. The results of the study showed that the phenomena of code switching and code mixing appeared a lot in conversation between Najwa Shihab and Maudy Ayunda.